Welcome :: Homework Help and Answers :: Mathskey.com

Recent Visits

    
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,179 questions

17,736 answers

1,437 comments

33,726 users

y+1=2/3​(x+6​) in standard form

0 votes
asked Nov 18, 2017 in ALGEBRA 1 by anonymous

1 Answer

0 votes

The equation

y + 1   =   (2/3)(x + 6)

3(y + 1)   =   2(x + 6)

3y + 3   =   2x + 12

2x + 12 - 3y - 3 = 0

2x - 3y + 9   =   0

2x - 3y  =  - 9

answered Dec 23, 2017 by homeworkhelp Mentor
edited Dec 23, 2017 by bradely

Related questions

...